2016
DOI: 10.1097/iae.0000000000000796
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Retinal Vein Occlusion With Central Serous Chorioretinopathy

Abstract: Central serous chorioretinopathy increases the risk of RVO. For CSCR patients, the authors recommend thorough retinal vessel evaluation, regular follow-up, and education regarding RVO for patients with CSCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…29 2.30), 32 and retinal vein occlusion (AHR ¼ 3.15, 95% CI ¼ 1.91-5.21). 33 Although no adequate explanation of the relationship between CSC and these cardiovascular diseases was identified in these previous studies, the results of the current study provide a possible explanation.…”
Section: Discussionmentioning
confidence: 52%
“…29 2.30), 32 and retinal vein occlusion (AHR ¼ 3.15, 95% CI ¼ 1.91-5.21). 33 Although no adequate explanation of the relationship between CSC and these cardiovascular diseases was identified in these previous studies, the results of the current study provide a possible explanation.…”
Section: Discussionmentioning
confidence: 52%
“…Central Serous Chorioretinopathy (CSCR) is idiopathic and often recurs. However, the mechanism of CSCR is unclear and it's reported that CSCR patients (>40 years) increased the risk of RVO ( 125 , 126 ). Regular review of CSCR patients may be the main approach to prevent the occurrence of RVO.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Therefore, several cohort studies have involved investigating the association between CSC and systemic diseases related with endothelial dysfunction. [24][25][26] Among them, a population-based cohort study demonstrated that CSC increases the risk of retinal vein occlusion. 26 Moreover, those authors emphasized that the relationship between CSC and retinal vein occlusion is based on inflammation processes.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Among them, a population-based cohort study demonstrated that CSC increases the risk of retinal vein occlusion. 26 Moreover, those authors emphasized that the relationship between CSC and retinal vein occlusion is based on inflammation processes. Nitric oxide production can be disrupted by inflammation processes in CSC and subsequently result in endothelial dysfunction, which indicates an association between CSC and retinal vein occlusion.…”
Section: Discussionmentioning
confidence: 99%